Synthesis, and prediction of molecular properties and antimicrobial activity ofsome acylhydrazones derived fromN-(arylsulfonyl)methionine - (:unkn) unknown (My University, 2016)
0

A series of 38 new acylhydrazones [3{40], derived from (2S)-4-(methylsulfanyl)-2-[[(4-methylphenyl)sulfonyl]amino]butanoic acid hydrazide [2], were synthesized and evaluated for their anti-HIV and antimicrobial activity withthe further aim to develop acylhydrazones carrying an amino acid side chain. All tested compounds possess strongeractivity against gram (+) bacteria. Compound23was found active against methicillin-resistantStaphylococcus aureus(MRSA) with a MIC value of 3.9?g/mL. The MIC value of compound30againstEnterococcus faecalis,Listeriamonocytogenes, andBacillus cereuswas 8?g/mL. A computational study for prediction of ADME and drug-likeproperties (solubility, drug-likeness, and drug score) as well as potential toxicity pro les of compounds2{40wasperformed using the Molinspiration online property calculation toolkit and Osiris Property Explorer. As most of ourcompounds meet Lipinski\'s rule of ve, they promise good solubility and permeability. According to Osiris calculations,the majority of our compounds are supposed to be nonmutagenic and nonirritating.
Keywords: Mühendislik, Kimya